Pragmatic functions of Christian expressions in spoken discourse - Verdonik, Darinka (Linguistica (Ljubljana), 2012)
Different kinds of pragmatic expressions in spoken discourse, such as discourse markers, interjections, topic orientation markers, pragmatic deictics, general extenders, etc., have attracted the attention of researchers over recent decades. However, expressions that have their origins within religions have not as yet been studied from the pragmatic perspective, even though in everyday conversation they are used in non-religious contexts and content-free manners more often than within a religious context. The present study is based on the GOS Slovenian reference speech corpus, and covers the more common Christian expressions used in the corpus data, namely: bog "God", bože "God", marija "Mary", madona "Madonna", jezus "Jesus", hudič "Devil", vrag "Devil". The study attempts to highlight the contexts in which these expressions are used, as well as the pragmatic functions they perform.
Keywords: analiza diskurza; analyse du discours; Corpus linguistics; expressions religieuses; govorjeni jezik; korpusno jezikoslovje; krščansko besedišče; linguistique de corpus; oral; Slovene; slovenščina; verski izrazi; vocabulaire chrétien